GE_GERICHTE C/27134/2009 vom 13. Dezember 2013 - GE Cour de justice (2013)
LIQUIDATION DU RÉGIME MATRIMONIAL; RÉGIME MATRIMONIAL ; RÉCOMPENSE(RÉGIME MATRIMONIAL); OBLIGATION D'ENTRETIEN | CPC.316.3; CC.200.1; CC.196; CC.204.2; CC.211; CC.214; CC.200.3; CC.206; CC.209; CC.125